The Role of M2 Pyruvate Kinase in the Screening of Bowel Inflammation - Ruswhandi -; Marcellus Simadibrata; Irsan Hasan (The Indonesian Society for Digestive Endoscopy, 2015)
Background: This is a study to determine if M2 Pyruvate Kinase (M2-PK) can be used to screen the presence of bowel inflammation.Method: The study design being used is diagnostic test. In this study, we recruited 76 participants and performed colonoscopy examination as a gold standard and faecal M2-PK as the examined procedure.Results: From the result of this study, we identified the important role of M2-PK to screen the presence of bowel inflammation with the cut-off point of 1.05 U/mL compared to colonoscopy as gold standard with the sensitivity of 86.2%, specificity 81.8%, positive predictive value 96.6%, and negative predictive value 50%.Conclusion: From the result of this study, we suggested M2-PK examination to screen bowel inflammation in patients with lower gastrointestinal tract problems.